Optimization of Biogas Production Process in Solid State Digesters in Semiarid Areas of Northern Tanzania - Mahushiab, Debora J; Muzukaa , Alfred NN; Machunda , Revocatus L (Tanzania Journal of Science, 2021)
Solid state digestion process has received much attention due to its low water requirements, making it preferred in semi-arid areas as well. In this study, the performance of the household solid state digesters was evaluated through monitoring of the feedstock mixing ratios and using the digester gas pressure as a measure of performance. Additionally, a batch study to verify the appropriate and optimal mixing ratio of feedstocks was also done. The mixing ratios of cow dung to water were 2:1, 3:1 and 4:1. Total solids determined were 120, 150 and 170 mg/g for the ratios 2:1, 3:1 and 4:1, respectively. Biogas yields for 2:1, 3:1 and 4:1 mixing ratios in laboratory batch mode were 21.4, 22.7 and 46.4 mL/gVS, respectively. These results from a practical scenario show a promising future of the technology which can be adopted by the solid state digester users living in dry areas Cowdung, Biogas, Mixing ratio, Batch solid state anaerobic digester.